SHIRODHARA IN THE MANAGEMENT OF VATIKA SHIRASHOOLA WITH SPECIAL REFERENCE TO CHRONIC DAILY HEADACHE: A REVIEW - Anuradha (International Journal of Applied Ayurved Research, 2017)
In Uttartantra, Acharya Sushruta has devoted separate chapters to Shiroroga and their manage-ment. This fact itself shows that Shirashoola has been a major problem to the physicians since long back. In modern medical science the drugs used in alleviating headache have been found to give temporary relief only and that too with some serious side effects like gastrointestinal prob-lems, dementia, weight gain, dry mouth, nausea, vomiting etc. Also some drugs are found to be addictive to patients. Therefore there arises a need to discover a non pharmacological therapy to alleviate shirashoola. Shirodhara is one such therapy in which medicated decoction or oil etc is poured onto forehead from a specific height for a stipulated duration of time. Present review pa-per highlights the importance and mode of action of shirodhara in the management of shirashoola.